Emergent electronic structure of CaFe2As2 - Khadiza Ali (Nature Portfolio, 2017)
Abstract CaFe2As2 exhibits collapsed tetragonal (cT) structure and varied exotic behaviour under pressure at low temperatures that led to debate on linking the structural changes to its exceptional electronic properties like superconductivity, magnetism, etc. Here, we investigate the electronic structure of CaFe2As2 forming in different structures employing density functional theory. The results indicate that the stability of the cT phase under pressure arises from the enhancement in hybridization induced effects and shift of the energy bands towards lower energies. The Fermi surface centered around Γ point gradually vanishes with the increase in pressure. Consequently, the nesting between the hole and electron Fermi surfaces associated to the spin density wave state disappears indicating a pathway to achieve the proximity to quantum fluctuations. The magnetic moment at the Fe sites diminishes in the cT phase consistent with the magnetic susceptibility results. Notably, the hybridization of Ca 4s states (Ca-layer may be treated as a charge reservoir layer akin to those in cuprate superconductors) is significantly enhanced in the cT phase revealing its relevance in its interesting electronic properties.